Boronia heterophylla is cultivated for cut flower production. Three cultivars dominate production, ‘Red’, ‘Cameo’, and ‘Moonglow’. A variety of colors and an extended flowering period are demanded by local and overseas markets. The aim of this study was to develop procedures for a Boronia heterophylla breeding program through intraspesific hybridization. This may yield progeny with desirable characteristics, ideally increased vigor, and a range of flower colors and flowering times. Nine pollinat - IDA AYU ASTARINI; GUIJUN YAN; JULIE ANNE PLUMMER (Bogor Agricultural University, Indonesia, 2011)
Boronia heterophylla is cultivated for cut flower production. Three cultivars dominate production, ‘Red’, ‘Cameo’, and ‘Moonglow’. A variety of colors and an extended flowering period are demanded by local and overseas markets. The aim of this study was to develop procedures for a Boronia heterophylla breeding program through intraspesific hybridization. This may yield progeny with desirable characteristics, ideally increased vigor, and a range of flower colors and flowering times. Nine pollination combinations were attempted, each self pollination and all reciprocal crosses. Seed set varied from 17 to 95%. Embryo rescue (was employed to produce hybrid plants using half strength Murashige and Skoog (MS) basal media and it was most successful (75%) 5-6 weeks after pollination. All shoots multiplied on media containing MS salts + NAA (0.1 mg/l) + BA (0.4 mg/l). All shoots transferred to medium containing half strength MS salts + NAA (4 mg/l) produced roots. Plantlets were acclimatized to sterile potting mix (in a small chamber within a glass house. This intraspecific hybridization system was very successful and plants were obtained for all pollination treatments except for selfed ‘Moonglow’. Embryo rescue may provide a system for germinating other species with difficult to germinate or dormant seed.